Mental Health Support for Hemodialysis Patients and Families: Needs, Programs, and Barriers - Puspa Wardhani; Fakrul Ardiansyah; Ruri Virdiyanti; Maulidah Maulidah; Suhendra Suhendra; Bernadette D. Quiambao (Borneo Scientific Publishing, 2026)
Patients undergoing long-term hemodialysis frequently experience significant psychological distress and psychosocial challenges. At the same time, mental health services within dialysis settings remain insufficiently integrated and often overlook the needs of family caregivers.This study aimed to explore the needs, existing programs, and barriers to mental health service implementation for hemodialysis patients and their families at St. Vincentius General Hospital, Singkawang. Using a qualitative approach, 26 participants were recruited through purposive sampling, comprising 10 hemodialysis patients, 10 family caregivers, and 6 nurses. Data were collected through semi-structured interviews, participatory observation, and document review, and were analyzed using thematic analysis.The analysis revealed three major themes. First, patients and families reported significant psychosocial needs stemming from emotional distress, challenges in treatment adaptation, and caregiver burden. Second, existing mental health services were limited, informal, and primarily delivered through therapeutic communication and spiritual support without structured screening, counseling, or referral mechanisms. Third, critical implementation barriers were identified, including limited clinical time, high nursing workloads, insufficient mental health training, low awareness among stakeholders, and a lack of standardized referral pathways. These findings underscore the urgent need for integrated, structured mental health services to enhance continuity of care and improve the well-being of hemodialysis patients and their families.